2004
DOI: 10.1016/j.ymthe.2004.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Ad-IFNα Causes Marked Regression of Human Bladder Cancer Growing Orthotopically in Nude Mice and Overcomes Resistance to IFN-α Protein

Abstract: We have produced prolonged, high local concentrations of interferon in vivo by intravesical instillation of adenoviruses encoding interferon-alpha (Ad-IFNalpha) together with the gene transfer-enhancing agent Syn3. We found sustained interferon protein levels for days, both in normal mouse urothelium and in human bladder cancer cells growing as superficial bladder tumors in nude mice using an orthotopic bladder model developed by us. Tumor burden in the bladder was determined utilizing cancer cells containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 14 publications
4
114
0
Order By: Relevance
“…7,8 In our initial study, we found that two daily 1 h intravesical administrations of Ad-IFNa at a concentration of 1 Â 10 11 particles/ml (P/ml), together with Syn3, produced a marked tumor regression in superficial human bladder tumors. 9 All other treatments including Syn3 alone, Ad-bgal/Syn3, Ad-IFN without Syn3, or the IFN protein alone at high concentration showed no effect on tumor growth. 9 In addition, these studies indicated that Ad-IFNa produced a strong bystander effect and surprisingly was effective in bladder cancer cells which were resistant to the IFN protein.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…7,8 In our initial study, we found that two daily 1 h intravesical administrations of Ad-IFNa at a concentration of 1 Â 10 11 particles/ml (P/ml), together with Syn3, produced a marked tumor regression in superficial human bladder tumors. 9 All other treatments including Syn3 alone, Ad-bgal/Syn3, Ad-IFN without Syn3, or the IFN protein alone at high concentration showed no effect on tumor growth. 9 In addition, these studies indicated that Ad-IFNa produced a strong bystander effect and surprisingly was effective in bladder cancer cells which were resistant to the IFN protein.…”
Section: Introductionmentioning
confidence: 92%
“…9 All other treatments including Syn3 alone, Ad-bgal/Syn3, Ad-IFN without Syn3, or the IFN protein alone at high concentration showed no effect on tumor growth. 9 In addition, these studies indicated that Ad-IFNa produced a strong bystander effect and surprisingly was effective in bladder cancer cells which were resistant to the IFN protein. 9 The protocol for our initial studies, 9 that is, to instill the Ad-IFN/Syn3 for 1 h on two consecutive days was based on optimization studies using Ad-bgal as a marker.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations